Pengaruh Penggunaan Tepung Buah Mengkudu terhadap Bobot Organ Pencernaan Ayam Pedaging - Nurhayati Nurhayati (Jurnal Agripet, 2010)
Effect of noni fruit powder on digestive organs weight of broiler chickensABSTRACT. The experiment aimed to determine the effect of using Noni fruit powder (NFP) up to 10 percent in the ration on digestive organs weight of male broiler chickens fed commercial feed. A hundred day old male broiler chickens were used in this experiment. Chickens were divided into five treatment groups; R0 (control, chickens fed commercial feed without offering NFP), R1 (the ration contained 2.5 % of NFP), R2 (the ration contained 5 % of NFP), R3 (the ration contained 7.5 % of NFP) and R4 (the ration contained 10 % of NFP). Each treatment group was replicated 4 times. Chickens were housed in the colony cages where 5 chickens each. The ration and drinking water were offered ad libitum. Parameters measured were feed intake, slaughter weight, gizzard weight, liver weight, small intestine weight and length. The results showed that using Noni fruit powder in the ration up to 10 percent caused no significant different effect on all parameters. It concluded that Noni fruit powder can be mixed into the ration up to 10 percent without any adverse effect on the digestive organs.